Language-By-Radio in Sub-Saharan Africa: Four Case Studies - Richmond, Edmun B. (IALLT Journal of Language Learning Technologies, 1982)
In the summer of 1981, the author was engaged in pedagogicalresearch in language program development for the governments of Senegaland The Gambia. During that period, he further participated in an eight countrylanguage teaching survey throughout West, Central, and EastAfrica, under the sponsorship of the United States International CommunicationsAgency. Included in that survey was an analysis of the useof radio broadcasts as a means to teach foreign languages. This articlewill describe the language-by-radio programs in four countries, i.e.,Senegal, Burundi, Rwanda, and Kenya. Of special interest is the use ofradio to teach English.